Visible light active Cu(3−x)Zn x SnS4 for efficient photocatalytic degradation of brilliant green dye - Ashmalina Rahman; Fazlurrahman Khan; James Robert Jennings; Young-Mog Kim; Mohammad Mansoob Khan (Scientific Reports)
Abstract Copper zinc tin sulfide (Cu(3−x)ZnxSnS4, CZTS) is an eco-friendly, non-toxic, and cost-effective photocatalyst composed of earth-abundant elements, offering a tunable narrow band gap that is ideal for environmental remediation. In this study, CZTS photocatalyst powders with varying Cu:Zn ratios (1:2, 2:1, and 2.5:1) were synthesized using a rapid microwave-assisted method and evaluated for their effectiveness in degrading organic pollutants in water. Structural and optical characterization confirmed the successful synthesis of the kesterite phase of CZTS for all compositions, with optical band gaps ranging from 2.21 to 2.30 eV. Amongst the studied Cu:Zn ratios, CZTS with a 2:1 Cu:Zn ratio exhibits the highest photocatalytic performance, degrading up to 91% brilliant green dye (BG) after 5 h of Xe-lamp irradiation. Reactive free radical scavenging/trapping experiments revealed that h+ played a dominant role in the degradation of BG. Based on these findings, a plausible mechanism of photocatalytic BG degradation using CZTS is proposed. These findings highlight the importance of compositional tuning in enhancing photocatalytic efficiency and demonstrate the potential of microwave-assisted synthesis as a straightforward and scalable method for producing high-performance CZTS photocatalysts for sustainable water purification applications.